Investigation of the EXAFS Cumulants of Silicon and Germanium Semiconductors by Statistical Moment Method: Pressure Dependence - Hieu, Ho Khac; Hung, Vu Van; Hung, Nguyen Van (Communications in Physics, 2011)
Pressure dependence of Extended X-ray Absorption Fine Structure (EXAFS) cumulants of silicon and germanium have been investigated using the statistical moment method (SMM). Analytical expressions of the first and second cumulants of silicon and germanium have been derived. The equations of states for silicon and germanium semiconductors have been also obtained using which the pressure dependence of lattice constants and volume of these semiconductors have been estimated. Numerical results using the developed theories for these semiconductors are found to be in good and reasonable agreement with those of the other theories and with experiment.